Indonesia’s Democracy in the 21st Century: A Book Review - Rahma Bachtiar, Farahdiba (Indonesian Perspective, 2017)
There are plenty of books wrote about Indonesia’s democracy by foreign scholars. Yet, many of them are very heavy read when it comes to politics. The book is an alternative. Intentionally wrote to offer brief overview about Indonesia’s, the book by McDonald indeed is presented to be ease for understanding yet contains fruitful topics on Indonesia’s democracy. His long experience as a journalist and writer of the classic book -Suharto’s Indonesia, as well as his journey to the country gave him adequate capacity to understand Indonesia better in the past and today. And thus it is why as mentioned before that he offers what he called “authoritative introduction”, because he is not a pure academia. Therefore, it is better not to expect depth analysis about any particular subject. But the novelty of the book lies on its details of some particular cases which not too often revealed by other books.